Perdas e desperdício de alimentos no setor gastronômico: proposta de uma matriz classificatória - Zaro, Marcelo (My University, 2022)
Both in the gastronomy and in the tourism and hospitality sectors, the commercial Food and Nutrition Units (UANs) cause many environmental impacts, because they use natural resources and generate solid, liquid, and gas residues. Food-based residues stand out as the generated solid residues. Hence, this research aims at proposing a classification matrix regarding food loss and waste (PDAs) in services provided by UANs. Thus, we have applied the Life Cycle Assessment (ACV) and used tools to Survey the Environmental Aspects and Impacts (LAIA) and Failure Mode and Effects Analysis (FMEA). Data collection that made the ACV and the matrix proposal feasible was carried out based on: a) the delivery of forms to ad hoc consultants graduated in Nutrition to attribute the gravity and facility indices of detection and solution of factors that are associated with the PDAs obtained from a literature review; and b) interviews with managers and direct observation in the managed UANs. As a result, we have obtained a matrix in the UANs performance regarding the control of PDAs between great and bad. The numerical amplitude that enabled this framework varied between 0 and 2.168, in which the highest value was associated with the worst possible performance. The elaborated classification matrix is expected to contribute so that the commercial UANs have access to a management and classification tool regarding its performance as to the PDAs combat, stimulating the search for continuous improvement of processes and generating, therefore, business differentiation, profitability and increase of sustainability in the gastronomic sector. In addition, the classification matrix represents an important ally for public policies that aim to control the PDAs, given it allows comparing different services provided by commercial UANs. [resumo fornecido pelo autor]
Tanto no setor da gastronomia quanto no setor de turismo e hospitalidade, as Unidades de Alimentação e Nutrição (UANs) comerciais são causadoras de impactos ambientais, pois utilizam recursos naturais e geram resíduos sólidos, líquidos e gasosos. Entre os resíduos sólidos gerados, destacam-se os de origem alimentar. Nesse sentido, esta pesquisa visa propor uma matriz classificatória quanto às perdas e ao desperdício de alimentos (PDAs) em serviços prestados por UANs. Para isso, procedeu-se à Avaliação de Ciclo de Vida (ACV) e ao uso das ferramentas de Levantamento de Aspectos e Impactos Ambientais (LAIA) e Análise de Modos e Efeitos de Falha (Failure Mode and Effects Analysis - FMEA). A coleta de dados que viabilizou a ACV e a proposição da matriz ocorreu mediante: a) a entrega de formulários a consultores ad hoc com formação em Nutrição para a atribuição de índices de gravidade e de facilidade de detecção e solução de fatores que se relacionam com PDAs obtidos a partir de revisão da literatura; e b) entrevistas com gestores e observação direta nas UANs geridas. Como resultado, obteve-se uma matriz com o desempenho de UANs quanto ao controle de PDAs, enquadrado entre ótimo e ruim. A amplitude numérica que permitiu esse enquadramento variou de 0 a 2168, sendo o maior valor associado ao pior desempenho possível. Espera-se que a matriz classificatória elaborada contribua para que as UANs comerciais tenham acesso a uma ferramenta de gestão e classificação do seu desempenho no que concerne ao combate de PDAs, estimulando a busca pela melhoria contínua dos processos e gerando, assim, diferenciação de negócio, lucratividade e aumento da sustentabilidade do setor gastronômico. Além disso, a matriz classificatória representa uma importante aliada das políticas públicas que visam ao controle de PDAs, já que permite comparar diferentes serviços prestados por UANs comerciais. [resumo fornecido pelo autor]
Keywords: Serviço de alimentação - Administração; Serviço de alimentação - Consumo; Desperdício (Economia); Resíduos sólidos; Política pública; Food service management; Food service - Consumption; Waste (Economics); Solid wastes; Public policy